Britain's Industrial Evolution: The Structuring Role of Economic Theory. Issue 1 (2nd January 2018) - Konzelmann, Sue; Fovargue-Davies, Marc; Wilkinson, Frank
Abstract: We trace the coevolution of industrial organization and the ideas and policies that have influenced Britain's industrial development from Alfred Marshall's pioneering work on the English industrial districts to the present. Then, we examine four contemporary districts — in footwear, motorsport, sparkling wine, and cyber security — that are internationally competitive, despite decades of ill-informed policy choices, if not neglect. We also investigate the case of British elite sport as a high-performance industrial cluster with potentially transferrable institutional arrangements, particularly with regard to the nature and role of the strategic lead body and the state, as well as relationships within the system. We conclude that Marshall's methodological and theoretical approach to understanding industrial organization — and his belief that industrial districts would coexist with other forms of industrial organization (rather than be superseded by them) — helps to explain the dynamism of contemporary British industrial districts, with important implications for Britain's industrial revitalization.